Human CD3+ T-cells with the anti-ERBB2 chimeric antigen receptor exhibit efficient targeting and induce apoptosis in ERBB2 overexpressing breast cancer cells - Munisvaradass, Rusheni; Subbiah, Suresh Kumar; Govindasamy, Chandramohan; Alnumair, Khalid S.; Mok, Pooi Ling (MDPI AG, 2017)
Breast cancer is a common malignancy among women. The innate and adaptive immune responses failed to be activated owing to immune modulation in the tumour microenvironment. Decades of scientific study links the overexpression of human epidermal growth factor receptor 2 (ERBB2) antigen with aggressive tumours. The Chimeric Antigen Receptor (CAR) coding for specific tumour-associated antigens could initiate intrinsic T-cell signalling, inducing T-cell activation, and cytotoxic activity without the need for major histocompatibility complex recognition. This renders CAR as a potentially universal immunotherapeutic option. Herein, we aimed to establish CAR in CD3+ T-cells, isolated from human peripheral blood mononucleated cells that could subsequently target and induce apoptosis in the ERBB2 overexpressing human breast cancer cell line, SKBR3. Constructed CAR was inserted into a lentiviral plasmid containing a green fluorescent protein tag and produced as lentiviral particles that were used to transduce activated T-cells. Transduced CAR-T cells were then primed with SKBR3 cells to evaluate their functionality. Results showed increased apoptosis in SKBR3 cells co-cultured with CAR-T cells compared to the control (non–transduced T-cells). This study demonstrates that CAR introduction helps overcome the innate limitations of native T-cells leading to cancer cell apoptosis. We recommend future studies should focus on in vivo cytotoxicity of CAR-T cells against ERBB2 expressing tumours.